A new heurisitc algorithm for minimizing the makespan on identical parallel machines - Öztürk, Serhat (My University, 2008)
Bilindiği üzere paralel makinelerde yayılma alanının (Cmax) minimum değerini kesin olarak polinom zamanda hesaplayacak bir yöntemin geliştirilmesi mümkün değildir. Bu nedenle en iyi sonuca yakın sonuçlar bulabilmek için sezgisel yöntemlerin uygulanması uygundur. Bu çalışmada özdeş paralel makinelerde yayılma alanının minimum değerini elde edecek, LPT (Longest Processing Time – En Uzun İşlem Zamanı) algoritmasından genelde daha iyi çözüm getirebilen bir algoritma oluşturmak hedeflenmiştir.Bilgisayar ortamında modellenen yeni algoritma ve LPT algoritmalarının performanslarının kıyaslanması için 1640 farklı problem çözülmüştür. İş sayısı, makine sayısı, iş zamanlarının ortalaması gibi özellikleri sırasıyla değiştirilmiş ve sonuçtaki değişimler gözlemlenmiştir. Sonuç olarak üniform dağılımdan elde edilen veriler ışığında, oransal olarak yeni algoritmanın LPT’ye göre daha iyi çözümler sağladığı hükmüne varılması için yeterli kanıt bulunduğu görülmüştür. Bu algoritma aynı zamanda olasılıklı durumlar için de modifiye edilmiştir.

A NEW HEURISTIC ALGORITHM FOR MINIMIZING THE MAKESPAN ON IDENTICAL PARALLEL MACHINES As known, it is not possible to develop an algorithm that can compute the exact value of the minimum makespan on identical parallel machines in polynomial time. Therefore heuristic methods are convenient to find near optimal solutions. In this thesis, it is aimed to compose a new heuristic algorithm to minimize the makespan on identical parallel machines. This algorithm can present better solutions than LPT (Longest Processing Time) algorithm in general. The computer models of the proposed and LPT algorithms are developed. 1640 different problems are solved using the two models to compare the performances of the algorithms. Numbers of jobs, numbers of machines or the mean of processing times are changed one at a time, while keeping the rest constant and, the variation in the makespan is observed.Finally it is concluded that there is sufficient evidence that the proposed algorithm provides better solutions than LPT in the light of the data collected from the uniform distribution.The proposed algorithm is also modified to the probabilistic cases.
Keywords: Algoritma; Paralel Makineler